2012
DOI: 10.7745/kjssf.2012.45.1.051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brevibacterium iodinum RS16 and Methylobacterium oryzae CBMB20 Inoculation on Seed Germination and Early Growth of Maize and Sorghum-sudangrass hybrid Seedling under Different Salinity Levels

Abstract: Salinity is one of the most relevant abiotic factor limiting crop yield and its net primary productivity. In addition, salinity induces an increased stress ethylene synthesis in plants which, in turn, exacerbate the responses to the stressor. Bacterial single or co-inoculation effect was tested using previously characterized plant growth promoting (PGP) bacteria Brevibacterium iodinum RS16 and Methylobacterium oryzae CBMB20 on maize and sorghum-sudan grass hybrid under different concentrations of NaCl. Non-ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…Inoculation of A. chroococcum enhanced the plumule length of Chinese cabbage significantly by 1.75 and 2.25 cm under salinity of 50 and 100 mM of NaCl, respectively. Similar results were shown by Kim et al (2012), they found that co-inoculation of Brevibacterium iodinum and Methylobacterium oryzae mitigated the salinity stress and promoted the root length of maize and sorghum seedling by 22.9% and 29.7%, respectively. However, under salinity level of 150 and 200 mM of NaCl, A. chroococcum did not show positive effect on the plumule length.…”
Section: Resultssupporting
confidence: 85%
“…Inoculation of A. chroococcum enhanced the plumule length of Chinese cabbage significantly by 1.75 and 2.25 cm under salinity of 50 and 100 mM of NaCl, respectively. Similar results were shown by Kim et al (2012), they found that co-inoculation of Brevibacterium iodinum and Methylobacterium oryzae mitigated the salinity stress and promoted the root length of maize and sorghum seedling by 22.9% and 29.7%, respectively. However, under salinity level of 150 and 200 mM of NaCl, A. chroococcum did not show positive effect on the plumule length.…”
Section: Resultssupporting
confidence: 85%
“…Seeds were agitated at 150 rpm with their spore suspension for 2 h at room temperature. The seeds were separated from the spore suspension using sterile tea mesh sieves and set as 10 seeds/dish [15]. The seeds were placed on sterile filter paper (Whatman No.…”
Section: Seed Inoculationmentioning
confidence: 99%
“…Using the sterile mesh sieve, 10 seeds were separated and each placed in a Petri dish lined by sterile filter paper (Whatman No. 1) [15]. Salinity and/or moisture conditions were provided by adding 5 ml of the sterile 0, 50, 100, and 150 mM NaCl solution.…”
Section: Seeds Inoculation Under Salinity Conditionsmentioning
confidence: 99%
“…plant growth. Several earlier studies also documented the single and co-inoculation increased plant height (Kim et al, 2012;Saber et al, 2012). We got the same kind of results with Adesemoye and Kloepper (2009), who reported that plant height significantly higher in bacterial inoculated treatment compared to non-inoculated treatment.…”
Section: Resultsmentioning
confidence: 84%